A new species of Postia (Polyporales, Basidiomycota) from China based on morphological and molecular evidence - Shen, Lulu; Cui, Baokai; Dai, Yucheng (Phytotaxa, 2014)
A new polypore, Postia duplicata, collected in Yunnan and Zhejiang provinces, is described and illustrated on the basis of morphological and molecular characters. Postia duplicata is characterized by pileate basidiomata with pale brownish to brown pore surface when bruised, duplex context, a monomitic hyphal system with clamped generative hyphae, presence of gloeocystidia in the hymenium, and cylindrical basidiospores (3.8–5.8 × 1.8–2.5 µm). Both morphological and molecular evidence confirmed the placement of the new species in Postia and showed its phylogenetic relationships.